2005
DOI: 10.1590/s0100-879x2005001200002
|View full text |Cite
|
Sign up to set email alerts
|

Protein-mediated surface structuring in biomembranes

Abstract: The lipids and proteins of biomembranes exhibit highly dissimilar conformations, geometrical shapes, amphipathicity, and thermodynamic properties which constrain their two-dimensional molecular packing, electrostatics, and interaction preferences. This causes inevitable development of large local tensions that frequently relax into phase or compositional immiscibility along lateral and transverse planes of the membrane. On the other hand, these effects constitute the very codes that mediate molecular and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Although still unresolved, rafts may be involved in membrane trafficking [121,135,136] and growth factor signalling [97, 137,138] in OLs. In these putative signalling platforms, classic MBP may facilitate the relay of signals from the plasma membrane to the cell interior [89, 126,132,139], perhaps indirectly by modulating the local physicochemical properties of the membrane [24,127,140,141] and of the underlying cytoskeleton [142][143][144][145][146]. It is known that there is an altered distribution of post-translationally modified components of MBP in MS [128,147].…”
Section: Drms In Myelin and Myelin-forming Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still unresolved, rafts may be involved in membrane trafficking [121,135,136] and growth factor signalling [97, 137,138] in OLs. In these putative signalling platforms, classic MBP may facilitate the relay of signals from the plasma membrane to the cell interior [89, 126,132,139], perhaps indirectly by modulating the local physicochemical properties of the membrane [24,127,140,141] and of the underlying cytoskeleton [142][143][144][145][146]. It is known that there is an altered distribution of post-translationally modified components of MBP in MS [128,147].…”
Section: Drms In Myelin and Myelin-forming Cellsmentioning
confidence: 99%
“…thus remains an open one [126,127,132,192]. The various posttranslational modifications of MBP may serve to target it and modulate its interaction with the myelin membrane, so as to define microdomains with specific physicochemical properties [24,127,132,140,141].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…It is interesting that the protein-free phospholipid domains having compositionally-independent melting show marked changes of their thermodynamically-correlated cluster sizes and distribution functions in the presence of the protein. This clearly points out the existence of a so far disregarded structural influence on a long-range scale among the coexisting phase domains on the thermodynamic level [168].…”
Section: Interactions Of Proteins With Sphingolipidsmentioning
confidence: 77%
“…By contrast the increase of transition enthalpy, with a slight increase of transition temperature, induced by MBP on the thermotropic behavior of gangliosides corresponds to a surface-mediated protein adsorption [166,167]. Statistical thermodynamic analysis of the phase transition process [168] revealed that increasing proportions of MBP induces large and broadly distributed glycosphingolipid-enriched clusters (in terms of the number of thermodynamicallycorrelated molecules) of the higher melting domains. On the other hand, in the presence of MBP, the segregated low-temperature (pure or highly phospholipid-enriched) domains become quite small and rather narrowly distributed.…”
Section: Interactions Of Proteins With Sphingolipidsmentioning
confidence: 93%
“…The study allowed concluding that PM originate from burned sugar cane leaves has an effect over some features of PS model systems and those properties have the potential to interfere in the perfect performance of these systems in biological environments. (Wiecek et al, 2008;Maggio et al, 2005;Gidalevitz et al, 2003;Lourenzoni et al, 2007). Inclusive em nosso grupo de pesquisa, tem-se demonstrado a utilidade dessa ferramenta na investigação da interação entre fosfolipídios com:…”
Section: Microscopy (Afm) and Fluorescence Lifetime Imaging Microscopmentioning
confidence: 99%